The Effect of Maternal Education and Knowledge on Stunting Incidence in Toddlers in Paya Baro Village, Meureubo District, West Aceh Regency - Darmawan Darmawan; Susy Sriwahyuni; Fikri Faidul Jihad; Siti Maisyaroh Fitri Siregar (Universitas Teuku Umar, 2022)
Maternal education and knowledge have an important role in influencing the incidence of stunting which is at risk from the mother's pregnancy to the first thousand days of life. The problem is the high stunting rate in Paya Baro village, which reaches 10.18%. The purpose of this study was to analyze the influence between education and knowledge variables on stunting events in Paya Baro Village, Meureubo District, West Aceh Regency. This research method uses an analytical quantitative method which is used to analyze the influence of education and knowledge of toddler mothers on stunting events with a sample of 50 pregnant women in Paya baro village, Meureubo District, West Aceh Regency and the results obtained were presented in table form. The results can be seen characteristics based on the education of pregnant women as much as (39.1%) not going to school (17.4%) elementary education (13%) junior high school education (13%) high school education (17.4%) undergraduates. Meanwhile, the knowledge of mothers with a good level of knowledge (34.5%) and a poor level of knowledge as much as (43.75). The education variables of pregnant women have a meaningful relationship with the incidence of stunting p = value <0.001 and there is a meaningful influence between the knowledge of pregnant women on the incidence of stunting p = value <0.003. Conclusion there is an influence of maternal education and knowledge on the incidence of stunting in toddlers in Paya Baro Village, Meureubo District, Aceh Regency having an increased risk of stunting problems due to low levels of education and poor knowledge can increase stunting in children. It is hoped that policymakers can improve stunting prevention programs through community empowerment.